Efficient LOD-SC-PML Formulations for Electromagnetic Fields in Dispersive Media - Ramadan, Omar (IEEE-Inst Electrical Electronics Engineers Inc, 2012)
Efficient locally one dimensional stretched-coordinate perfectly matched layer (LOD-SC-PML) formulations are presented for truncating open region dispersive finite difference time domain (FDTD) applications. The field equations in the PML regions are implemented with the minimal additional auxiliary variables that will be computed only in one of the LOD-FDTD scheme stages. It has been shown that the proposed formulations are computationally efficient more than the alternating direction implicit SC-PML counterpart, while maintaining approximately the same numerical performance.
Keywords: Dispersive materials; finite difference time domain (FDTD); locally one dimensional (LOD); stretched-coordinate perfectly matched layer (SC-PML)